Answer:
f^(-1)(x) = (x-b)/m or x/m - b/m
Step-by-step explanation:
f(x) = y = mx + b
To find the inverse function, interchange x and y and solve for y, i.e.
x = my + b
my = x-b
y = (x-b)/m = x/m - b/m
Answer:
The answer is 1 or infinite solutions
Step-by-step explanation:
When you plug in the value of -5.5 into the equation, you will eventually end up with -17.5=-17.5, making the answer infinite or 1.
The answer is......... 27
Answer:
c. -oo < x < -1
Step-by-step explanation:
according to the graph the function possitive
=> y > 0 , and x < -1
Answer:
the ans is 9/10
Step-by-step explanation:
hope it helps u .........